(untitled) (University of Khartoum Journal of Agricultural Sciences, 2023)
he objectives of this study were to determine the growthperformance and carcass traits of turkeys under semi intensive system in theSudan. Atotal of 100 unsexed turkey growers from the commercial breed(B.U.T. Big 6) were used during 7 th June to 6 th August, 2011. Birds were keptin an open sided deep litter poultry house at the University of Bahri Farmfrom 9 to 16 weeks of age and fed on turkey grower and finisher diets.Results of feed intake and body weight showed a consistent increase withincrease in age. Performance results showed that turkey had 2.42 kg, 6.64 kg,79.49 g, 1.5 kg/ bird/ day, 2.8 and 4%, starting weight, finishing weight,average daily gain, average feed intake; average feed conversion ratio (FCR)and total mortality, respectively. Results also showed that turkey had 6.91 kg,5.03 kg, 76.98%, 14.37%, 14.2% and 33.4% slaughter weight, carcassweight, dressing percentage and thigh, drumstick and breast weights aspercentage of carcass weight, respectively. Males obtained significantlyheavier slaughter, carcass, thigh, drumstick and breast weights than females.On the other hand PH, WHC and cooking loss were 5.63, 36.6 and 2.05,respectively. It can be concluded that, the rearing of B.U.T. Big 6commercial breed of turkey is possible under semi intensive system in theSudan. Further studies are needed to determine turkey performance andcarcass attributes under range and intensive systems of management using thesame breed or other turkey breeds.